Mycoplasma pneumoniae infection and neurological disease. Issue 5 (November 1993) - Thomas, N H; Collins, J E; Robb, S A; Robinson, R O
Abstract : The cases are reported of 13 children seen over a 22 month period who presented with a variety of acute neurological illnesses associated with Mycoplasma pneumoniae infection. Although presentation with a decreased level of consciousness or seizures was common, psychosis, hemiparesis, cranial nerve palsies, and Guillain-Barré syndrome were also seen. In contrast with published reports, only one child had an associated chest infection. Although some children have been left with residual disability, most have made a complete recovery. In this recent experience, M pneumoniae is a not rare cause of neurological illness in childhood and may present in unusual ways.